A Study on Various Conditions of Alkali Activated Mortar Mixture for Rheological Behavior - cheol Lee, Gun; Han, Dongyeop; young Lee, Gun; young Lee, Soo; joe Yoon, Seung (International Journal of Engineering and Technology, 2018)
In this research, the influence of binder proportions and hardening agent conditions on fluidity of alkali activated mortar is evaluated quantitatively. According to the results, the influence of binder proportions on viscosity of alkali activated mortar was 0 to 24 Pa.s, while the influence of hardening agent on viscosity of alkali activated mortar was 0 to 52 Pa.s. Thus, in this research scope, the degree of influence on fluidity of alkali activate fiber reinforced composite can be suggested that the hardening agent proportion was higher than the binder proportion.Â